Genetic and phenotypic parameters for female broiler lines - Ledur, Mônica Corrêa; Schmidt, Gilberto Silber; de Figueiredo, Élsio Antônio Pereira; de Ávila, Valdir Silveira; Fiorentin, Laurimar (Pesquisa Agropecuaria Brasileira, 1994)
Data included information on 3226 KK and 3373 PP female broiler lines under development at the Brazilian National Swine and Poultry Research Center, to estimate the heritability (h2), genetic (rg) and phenotipic correlations (rp) for (and between) weight at 42 days as well of age (P42), as egg production from 25 to 40 weeks of age (PD), egg weight at 28 (PO28), 32(PO32) and 37 (PO37) weeks of age, average egg weight (PMO), fertility (FERT), and hatchability rates (ECLO). The heritability estimates for P42, PD, PMO, FERT and ECLO were respectively .26 ± .05; .30 ± 06; .15 ± .04; .50 ± 01 and .06 ± .04 for KK, and .44 ± .07; .31 ± 0.6; 38 ± 07; .23 ± .05 and .13 ± .04 for PP. The h2 were high in both lines, for all traits but PMO in KK and ECLO in KK and PP. The rg were negative and low in PP and practically null in KK, except for rg between PD and PMO (-.41 ± .15).